Labial swelling: a rare presentation of pubic bone tuberculosis. (April 2017) - Shende, Prajakta; Gandhewar, Manisha; Gaikwad, Pradip; Nanaware, Sandip; Risbud Joshi, Prachi
Tuberculosis (TB), being a global health problem, represents variedly. Its presentation as a labial swelling secondary to pubic bone TB has been reported rarely in literature. We report a case of pubic bone TB presenting as a labial swelling in a woman of reproductive age. Early diagnosis with fine needle aspiration cytology, acid-fast bacillus (AFB) staining, AFB culture and magnetic resonance imaging with early initiation of treatment resulted in a favourable outcome.